Sports events planning considerations post COVID-19 - Finnoff, J. (USOPC Guidance: Return to Training and Sport Event Planning, 2020)
The USOPC is dedicated to protecting the health and safety of Team USA. The purpose of this document is to provide sports organizations (including National Governing Bodies [NGBs]) with information they can use to assist them with planning a sports event in the context of COVID-19. As a guideline meant to be used by sports as varied as archery and judo in locations as diverse as Minot and New York City by athletes and organizations with vastly different resources, this document cannot be prescriptive; rather, it should spark thoughtful deliberation among event planners to create their own unique event plan that is specific to their sport and situation. These recommendations may not be practical for junior or lower level amateur events. Many of the recommendations rely upon rules and regulations set forth by public health authorities, which will be different across the country and around the world. Furthermore, athletes, staff, media and spectators may travel to the event from around the world, thus increasing the risk of introducing COVID-19 into the event. In addition to the logistical challenges of planning an event in the context of COVID-19, there are also ethical and societal considerations that are beyond the scope of this document. These include, but are not limited to: o When is the rate of community COVID-19 transmission, and therefore the risk of infection, low enough to allow a sports event? o If the event is restricted to only athletes and essential support staff, can adequate testing of this group be performed to limit their risk of contracting COVID-19 during the event? o Is it appropriate for COVID-19 testing to be used for athletes and staff of a sports event when there are national and worldwide shortages of these tests? o Can event management mandate testing of athletes and essential support staff in order to participate in the competition? o Can event management exclude athletes from competing in the competition if they test positive for COVID-19 and/or present with signs and symptoms of COVID-19? o Is it appropriate for athletes, event staff and spectators to be supplied with or use personal protective equipment (PPE) meant for medical personnel when there is a worldwide shortage of PPE? o Should or can you restrict athletes from participating in an event if they travel from a location with active community transmission of COVID-19? Finally, although the young and healthy tend to have less severe cases of COVID-19, every case of this disease is potentially life-altering or deadly, particularly in those with risk factors that may occur in our Olympic or Paralympic athletes such as asthma, hypertension, diabetes, liver disease, kidney disease, immune suppression, or neurologic disorders affecting respiration. Furthermore, many essential support staff and spectators will have one or more of these risk factors plus additional risk factors such as age > 65. Even when no or very limited active transmission of COVID-19 is occurring in a specific region, it is likely that easing of public health restrictions or allowing people to travel to the event from distant sites will result in re-introduction of COVID-19 infections into the community and "second wave" outbreaks. Until COVID-19 is either eradicated, a vaccine is developed, or a cure is found, there is no way of completely eliminating the risk of fatal infection. This should always be in the forefront of your mind when planning your event.